(untitled) (Baltic Journal of Sport and Health Sciences, 2013)
Research background and hypothesis. Physical inactivity of patients with epilepsy is associated with the course of the disease, treatment, preconceived attitudes and myths that their physical activity might be dangerous and cause seizures (Steinhoff et al., 1996; Nakken, 2001 ). The aim of our research was to examine the links between the psychosocial problems of patients’ with epilepsy, their hysical activity, self-reported quality of life as well as their connection with patients’ age. Research methods. The participants were 209 patients with epilepsy from three different regions (Šiauliai, Panevėžys and Pasvalys) of Lithuania. The subjects were selected with the help of quantitative closed-type survey – QOLIE-89 and IPAQ international questionnaire. The research findings were compared between two age groups: younger (20–39 years of age) and senior (40–59 years of age) subjects. Research results. The main psychosocial problems for patients with epilepsy were concerns about possible injuries during the seizures, experience of shame and other social restraint, health problems that might occur as a result of taking antiepileptic drugs for a long period of time, negative effects of antiepileptic drugs and memory impairments. These problems were more common among younger respondents (p < 0.05). Physical activity levels in patients with epilepsy were inadequate and different. The main factor that contributed to these differences was patients’ age. Younger respondents trained more in their leisure time, while seniors spent more time reading or sleeping (p = 0.002).Younger patients lacked knowledge about the most appropriate types of physical activities, senior respondents were inactive were to the disapproval of medical professionals and their health problems (p = 0.006). Younger respondents evaluated their lifestyle as good enough more often than seniors. Discussion and conclusion. Psychosocial problems and physical inactivity of patients with epilepsy were connected with their age. Younger respondents more often than seniors were physically active and their self-reported quality of life was good. Keywords: age of patients with epilepsy, social problems, physical activity, evaluation of lifestyle.